EXPRESSING FAILURE OF LOVE WITH REFERENCE TO SONG LYRIC BY NIKI ZEFANYA’S NICOLE ALBUM - Ida Ayu Regita Triana Putri; I Made Netra; Ni Luh Putu Krisnawati (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2025)
This study entitled Expressing Failure of Love with Reference to Song Lyrics Niki Zefanya’s ‘Nicole’ Album aims to identify hyperbole representations and analyze the meaning. The data were taken from all songs in an album of Niki Zefanya’s album namely ‘Nicole’. The song lyrics were taken from Genius website. This study applied the documentation method and note-taking technique. The lyrics of the song were selected into those that represent hyperbole. This study was analyzed using descriptive qualitative methods to examine the data. The theories applied in this study were the theory of figurative language by Knickerbocker and Reninger, hyperbole forms by Claridge, and the theory of meaning by Leech. The analysis was presented informally. The analysis used descriptive analysis written in paragraph form. This study focused on finding three out of seven forms of hyperbole, those are single word hyperbole, phrasal hyperbole, and clausal hyperbole, and also focused on thematic meaning. The result of the study shows that there are representations of hyperbole and also found gradations in the severity of Niki's failure of love between all the songs in the album. Expression of failure of love can be divided into tender, ordinary, and harsh.